Studi In Silico Senyawa Bioaktif Ekstrak Curcuma longa sebagai Inhibitor Protein LASR pada Bakteri Pseudomonas aeruginosa - Nur Adillah; Ahadul Putra (MASALIQ, 2026)
Pseudomonas aeruginosa is an opportunistic pathogenic bacterium that employs a quorum-sensing mechanism mediated by the LasR protein to regulate biofilm formation and virulence. This study aims to analyze the potential of bioactive compounds from Curcuma longa as inhibitors of the LasR protein through an in silico approach. The study employed a computational approach using molecular docking to predict interactions between the ligands and the LasR protein. The analysis was followed by the prediction of physicochemical properties based on Lipinski’s Rule of Five and the evaluation of pharmacokinetic and toxicity profiles using ADMET parameters. The molecular docking results showed that all compounds had negative docking scores ranging from −6.9297 to −9.5288 kcal/mol. Curcumin and demethoxycurcumin exhibited the strongest binding affinities, with docking scores of −9.5288 and −9.5189 kcal/mol, respectively. All compounds met the criteria of Lipinski’s Rule of Five and demonstrated reasonably favorable ADMET profiles, although a moderate potential for toxicity was identified based on the AMES mutagenicity and human hepatotoxicity parameters. This study concludes that the bioactive compounds of Curcuma longa, particularly curcumin and demethoxycurcumin, have the potential to be developed as candidate inhibitors of the LasR protein. These findings provide a computational basis for compound structure optimization and further research through in vitro and in vivo testing to validate their effectiveness and safety as LasR inhibitors.